Selayang Pandang Perbuatan Main Hakim Sendiri menurut Hukum Islam dan Hukum Positif - Anam, Rohmatul; Fauzi, Tazkia Amelia; Setyorini, Tutut Dwi (LPPM Universitas Terbuka, 2024)
Violence usually occurs because of an incident that makes an individual or group of people anxious about another individual or group who commits a crime or causes trouble in their environment. Among them is the case that happened to Edwin Hermansyah Bin Suherman in Decision Number 8/Pid.B/2019/PN.Tgl. This paper tries to answer how the views of Islamic criminal law and positive law respond to the judge's decision regarding Decision Number 8/Pid.B/2019/PN.Tgl. This research is a normative research which contains a description of the problem under study based on cases taken from court decisions and legal literature as material for analysis using a case approach and literature techniques. The results of this study indicate that; First, the decision Number 8/Pid.B/2019/PN.Tgl stated that the sentence handed down by the judge was not in accordance with the concept of qisas in Islamic Criminal Law. Second, Indonesia's Positive Law views the actions of the Main Judge as included in the category of persecution where the punishment for perpetrators of ordinary abuse is regulated in the Criminal Code. Suggestions from this study are; First, every community should have legal awareness not to take vigilante actions because the judge is the one who has the right to adjudicate a problem. Second, restitution should be included in the sentence given to the Defendant so that the criminal law is more progressive by taking into account the loss and recovery of the victim.